2020
DOI: 10.1002/jbmr.4776
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment and Effect of Discontinuation of Calcifediol in Postmenopausal Women with Vitamin D Deficiency: A Randomized Trial

Abstract: Vitamin D plays a major role in bone health and probably also in multiple extraskeletal acute and chronic diseases. Although supplementation with calcifediol, a vitamin D metabolite, has demonstrated efficacy and safety in short‐term clinical trials, its effects after long‐term monthly administration have been studied less extensively. This report describes the results of a 1‐year, phase III‐IV, double‐blind, randomized, controlled, parallel, multicenter superiority clinical trial to assess the efficacy and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 46 publications
4
11
0
Order By: Relevance
“…Calcifediol may well be an alternative to the use of vitamin D supplementation [ 14 , 15 ]. Calcifediol is absorbed by intestinal cells, transported through the portal vein and is, therefore, immediately accessible to the circulation; meanwhile, native vitamin D is transported more slowly by chylomicrons via the lymphatic system.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Calcifediol may well be an alternative to the use of vitamin D supplementation [ 14 , 15 ]. Calcifediol is absorbed by intestinal cells, transported through the portal vein and is, therefore, immediately accessible to the circulation; meanwhile, native vitamin D is transported more slowly by chylomicrons via the lymphatic system.…”
mentioning
confidence: 99%
“…This potency is 6–8 times higher than vitamin D when the baseline serum 25OHD is higher or when large doses are compared [ 17 ]. Thus, clinical trials comparing the efficacy and safety of calcifediol and cholecalciferol in vitamin-deficient situations in the short and long term have reported that calcifediol is more effective; indeed, it sees a more rapid onset of action compared to the monthly administration of cholecalciferol, and possesses no associated safety concerns [ 14 , 15 ]. Long-term calcifediol treatment produces stable and sustained 25 (OH) D concentrations; however, as with “vitamin” D, the withdrawal of treatment leads to a steep decline in 25 (OH) D levels compared to pre-treatment levels [ 15 , 18 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2) Decision tree: The decision tree is a method for supervised learning that can effectively address classification and regression problems, primarily in solving classification tasks [18]. The terminology implies its utilization of a tree-like diagram to present predictions derived from a sequence of feature-driven divisions.…”
mentioning
confidence: 99%
“…(3) where, y represents the predicted output, b0 represents the bias or intercept term, and b1 represents the single input value (x) coefficient. Each input data column contains a b coefficient (a constant real value) that must be learned from your training data [18].…”
mentioning
confidence: 99%